Pengembalian Investasi pada Usahatani Selada Hidroponik dengan Metode Deep Flow Technique (DFT) dan Nutrient Film Technique (NFT) - Afriyanti Afriyanti; Novitri Kurniati; Edi Efrita; Elni Mutmainnah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
People with limited land or in urban areas can use the land for plant farming using hydroponics. Hydroponics is farming using water enriched with plant nutrients as a growth media. This system has been popular due to its efficiency in using water, land, time, and space. It also allows plant growth quickly and under controlled conditions. One of the vegetables that has the potential to be cultivated with a hydroponic system is lettuce (Lactuca sativa L). The nutrients in vegetables, especially vitamins and minerals, cannot be substituted by staple foods so that they can suffice the need for vegetables for the community. This study analyzes the return on investment and profit in hydroponic lettuce farming. The research method is a case study, and the data analysis technique used is investment costs, variable costs, income production, Return on Investment (ROI), and Payback Period (PP). The results showed that the hydroponic farming Deep Flow technique (DFT) method incurred costs of Rp54.730.590,48 and income of Rp9.266.566,52, and the Nutrient Film Technique (NFT) method incurred costs of Rp59.655.572,78 and received income of Rp6.769.306,45. The DFT technique has a Return On Investment (ROI) value of 16.9%, the NFT technique is 10.9%, and the DFT technique has a Payback Period (PP) of 5.89, while the NFT is 9.13.